Dynamic Weighted Idle Time Heuristic for Flowshop Scheduling. Issue 1 (April 2020) - Zainudin, A.S.; Bareduan, S.A.; Isa, N.A.
Abstract: Flowshop scheduling is used to determine the optimal sequence of n jobs to be processed on m machines in the same order. The objective of this paper is to minimize the makespan for group of jobs waiting in the process system. It proposed a new heuristic that apply dynamic weighted idle time (DWIT) that used several weight factor values as a multiplication factor of the total idle time. The result shows that the average percentage errors and standard deviation for DWIT heuristic are smaller compared to the NEH (Nawaz, Enscore and Ham) and it achieved more than 50% of optimum answer. Therefore, this DWIT heuristic has great potential to outperform the NEH heuristic.